IMPLEMENTATION OF OWNERSHIP OBLIGATIONS TRADITIONAL MARKET MANAGEMENT BUSINESS PERMITS IN ROKAN HULU REGENCY - Lubis, Roy Hakim; ansah, Ardi; Azmi, Bahrum (EKSEKUSI, 2024)
This research aims to analyze the implementation of the obligation to own a permit and analyze the factors that hinder it as well as efforts to overcome the obstacles in Rokan Hulu Regency. This type of research is sociological/empirical legal research. The approaches used are the statutory approach, case approach and historical approach with qualitative analysis methods. The results of the research show that firstly, the implementation of permit ownership obligations has not gone well. Second, inhibiting factors: legal factors, local government officials, facilities/facilities and the community. Third, efforts to overcome obstacles: legal factors, namely that it is best to simplify the permit requirements and procedures in regulations. regional government apparatus factors, namely that the government should be able to prioritize the use of appropriate budgeting; the government should carry out frequent outreach; It would be better if there was an appropriate division of tasks for the implementation of order and law enforcement, it would be better to increase supervision and guidance so that everyone has permits. the facilities/facilities factor is that it is better to increase the budget. Community factors, namely, it is better to implement strict sanctions so that there is a deterrent effect.Keywords: Implementation, IUP2T, Traditional Markets